The Idea of Education and the Contemporary World - Petrovic, Aleksandar M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In a copious introduction to the very problem of education, the author of the study — The Philosophy of Education (Belgrade: Serbian State Publisher of Textbooks, Belgrade, 2016), Milan Uzelac, describes all the main articulated moments, which formed and directed the development of education on a social and historic level. The bases of his conceptions of education are phenomenological, elaborated in a methodological continuum. Through a thouroughful critical review of the current, in general very disappointing state of education in our country, Uzelac points to new, possible directions of development of education.